The Wage Premium of Communist Party Membership: Evidence from China - Hongjian Wang; Plamen Nikolov; Kevin Acker (Institute of Labor Economics (IZA), 2019)
Social status and political connections may confer large economic benefits on an individual. Previous studies focused on China have examined the relationship between Communist Party membership and earnings and found a positive correlation. However, the correlation could be partly or totally spurious. Using data from three surveys spanning three decades, we estimate the causal effect of Chinese Communist Party membership on monthly earnings in China. We find that, on average, membership in the Communist Party of China increases monthly earnings and the wage premium has grown in recent years. We explore potential causes and discover evidence that improvements in social networks and social rank, acquisition of job-related qualifications, and greater life satisfaction likely play important roles in increased earnings.
Keywords: D31; J31; P2; 330; wage premium; political status; China; Communist Party